PENGARUH PRAKTEK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA PENYULUH KELUARGA BERENCANA PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROVINSI SULAWESI TENGGARA - Musdalifah Musdalifah (Pascasarjana Universitas Halu Oleo, 2022)
This study aims to (1) determine and examine the simultaneous effect of human resource management practices, namely education and training, performance allowances, and career development, on the performance of Penyuluh Keluarga Berencana representing the BKKBN Southeast Sulawesi Province. (2) To determine and examine the effect of education and training on the performance Penyuluh Keluarga Berencana for the BKKBN Representatives of Southeast Sulawesi Province. (3) To find out and test the effect of the performance allowance on the performance Penyuluh Keluarga Berencana of the BKKBN Representative of the Southeast Sulawesi Province. (4) To find out and test the effect of career development on the performance of the Penyuluh Keluarga Berencana of the BKKBN Representative of the Southeast Sulawesi Province. (5) To find out the variables that have the most influence on the performance PenyuluhKeluarga Berencana of the BKKBN Representative of the Southeast Sulawesi Province. The design of this study used an explanatory research design (Explanatory Research). This study uses a survey research approach that uses sample data by distributing questionnaires (questionnaires). Determination of the sample is carried out in stages, namely identifying the number of population units (number of PKB) in each Regency/City, determining the number of sample units (size) as a whole from the total population using the formula, Determining the number of sample units (sample size) in each district/city proportionally so that obtained 166 samplesThe results of the analysis and discussion state that the practice of human resource management which includes education and training, fairness-based performance allowances, and career development simultaneously has a positive and significant effect on the performance of Family Planning Extension Officers at the BKKBN Representative Office of Southeast Sulawesi Province. Education and training partially have a positive and significant effect on the performance of Family Planning Extension Officers at the BKKBN Representative Office of Southeast Sulawesi Province. The performance allowance has no significant effect on the performance of the Family Planning Extension Officer at the BKKBN Representative Office of Southeast Sulawesi Province. Career development has a positive and significant effect on the performance of the Family Planning Extension Officer at the Southeast Sulawesi Province BKKBN Representative Office.